2017
DOI: 10.1002/ps.4617
|View full text |Cite
|
Sign up to set email alerts
|

Interference of allelopathic rice with penoxsulam‐resistant barnyardgrass

Abstract: Allelopathic rice can interfere with the growth of penoxsulam-resistant barnyardgrass through allelochemical-mediated root interactions. This type of allelopathic interference may provide a non-herbicidal alternative for herbicide-resistant weed management in paddy systems. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Momilactone B, which is produced by Oryza sativa , has been studied in soil experiments. It was found that the penoxsulam‐resistant barnyardgrass could be inhibited through interactions with the roots of Oryza sativa , due to production of this diterpene . In the case of momilactone A, Xu et al demonstrated that copalyl diphosphate synthase 4 and kaurene synthase‐like 4 are involved in the production of this diterpene.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Momilactone B, which is produced by Oryza sativa , has been studied in soil experiments. It was found that the penoxsulam‐resistant barnyardgrass could be inhibited through interactions with the roots of Oryza sativa , due to production of this diterpene . In the case of momilactone A, Xu et al demonstrated that copalyl diphosphate synthase 4 and kaurene synthase‐like 4 are involved in the production of this diterpene.…”
Section: Chemistrymentioning
confidence: 99%
“…It was found that the penoxsulam-resistant barnyardgrass could be inhibited through interactions with the roots of Oryza sativa, due to production of this diterpene. 131 In the case of momilactone A, Xu et al 132 demonstrated that copalyl diphosphate synthase 4 and kaurene synthase-like 4 are involved in the production of this diterpene. Consequently, these synthases provide molecular targets for the future genetic manipulation of rice to improve its allelopathic capabilities.…”
Section: Diterpenesmentioning
confidence: 99%
“…In addition, resistance indices to penoxsulam have been reported to reach the values of 28.1 and 13.7 for E. phyllopogon and E. crus-galli, respectively [41]. E. crus-galli populations resistant to penoxsulam were also found in the studies of Yang et al [42] and Le et al [43]. In another study, the efficacy of penoxsulam was low against E. crus-galli accessions since it ranged from 25% to 32% for plants derived from seeds collected from plots treated with penoxsulam [44].…”
Section: Discussionmentioning
confidence: 72%
“…For instance, the allelopathic rice PI312777 can release allelochemicals into the soil and inhibit the growth of paddy weeds [24,27]. The allelopathic rice Huagan-3 can interfere with the growth of penoxsulam-resistant barnyardgrass through allelochemical-mediated root-root interaction [33]. In addition, decline of barnyardgrass root growth is due to shift in microbial diversity and community structure shaped by the root exudates of the allelopathic rice [26].…”
Section: Root Proliferation Response To Neighbouring Roots Of Allelopmentioning
confidence: 99%
“…This severity of the issue calls for immediate solutions and an investigation into the biological and ecological mechanisms of its competitiveness with rice. Fortunately, some varieties of O. sativa as PI312777 and Huagan-3 exhibit high allelopathic activity for paddy weeds and herbicide-resistant barnyardgrass [32,33]. Thus, results from root-mediated interactions between allelopathic rice and barnyardgrass enable us to consider this as a new mechanism of root recognition in plants.…”
Section: Introductionmentioning
confidence: 99%